Collapsin Response Mediator Protein 4 (CRMP4) Facilitates Wallerian Degeneration and Axon Regeneration following Sciatic Nerve Injury - Girouard, Marie Pier (2020)
In contrast to neurons in the CNS, damaged neurons from the peripheral nervous system (PNS) regenerate, but this process can be slow and imperfect. Successful regeneration is orchestrated by cytoskeletal reorganization at the tip of the proximal axon segment and cytoskeletal disassembly of the distal segment. Collapsin response mediator protein 4 (CRMP4) is a cytosolic phospho-protein that regulates the actin and microtubule cytoskeleton. During development, CRMP4 promotes growth cone formation and dendrite development. Paradoxically, in the adult CNS, CRMP4 impedes axon regeneration. Here, we investigated the involvement of CRMP4 in peripheral nerve injury in male and female Crmp4/ mice following sciatic nerve injury. We find that sensory axon regeneration and Wallerian degeneration are impaired in Crmp4/ mice following sciatic nerve injury. In vitro analysis of dissociated dorsal root ganglion (DRG) neurons from Crmp4/ mice revealed that CRMP4 functions in the proximal axon segment to promote the regrowth of severed DRG neurons and in the distal axon segment where it facilitates Wallerian degeneration through calpain-dependent formation of harmful CRMP4 fragments. These findings reveal an interesting dual role for CRMP4 in proximal and distal axon segments of injured sensory neurons that coordinately facilitate PNS axon regeneration.